Ways to Help and Ways to Hinder: Governance for Effective Adaptation to an Uncertain Climate - Loring, Philip A.; Gerlach, S. Craig; Atkinson, David E.; Murray, Maribeth S. (ARCTIC, 2011)
This paper compares two case studies in Alaska, one on commercial fishers of the Bering Sea and Aleutian Islands region and the other on moose hunters of Interior Alaska, to identify how governance arrangements and management strategies enhance or limit people’s ability to respond effectively to changing climatic and environmental conditions. The two groups face similar challenges regarding the impacts of a changing climate on wild fish and game, but they tell very different stories regarding how and under what conditions these impacts challenge their harvest activities. In both regions, people describe dramatic changes in weather, land, and seascape conditions, and distributions of fish and game. A key finding is that the “command-and-control” model of governance in the Alaska Interior, as implemented through state and federal management tools such as registration hunts and short open seasons, limits effective local responses to environmental conditions, while the more decentralized model of governance created by the Limited Access Privilege systems of the Bering Sea allows fishers great flexibility to respond. We discuss ways to implement aspects of a decentralized decision-making model in the Interior that would benefit hunters by increasing their adaptability and success, while also improving conservation outcomes. Our findings also demonstrate the usefulness of the diagnostic framework employed here for facilitating comparative crossregional analyses of natural resource use and management. Ce document établit une comparaison entre deux études de cas effectuées en Alaska, l’une portant sur les pêcheurs commerciaux de la mer de Béring et de la région des Aléoutiennes et l’autre, sur les chasseurs d’orignaux de l’intérieur de l’Alaska. Cette comparaison avait pour but de déterminer comment les ententes de gouvernance et les stratégies de gestion rehaussent ou restreignent l’aptitude des gens à réagir de manière efficace au changement climatique et aux conditions environnementales. Dans le cas des deux ...